Characterization of Influenza A Virus Infection in Mouse Pulmonary Stem/Progenitor Cells - Chao, Tai-Ling; Gu, Sing-Yi; Lin, Pi-Han; Chou, Yu-Tien; Ling, Thai-Yen; Chang, Sui-Yuan (Frontiers in Microbiology, 2020)
The pulmonary stem/progenitor cells, which could be differentiated into downstream cells to repair tissue damage caused by influenza A virus, have also been shown to be the target cells of influenza virus infection. In this study, mouse pulmonary stem/progenitor cells (mPSCs) with capability to differentiate into type I or type II alveolar cells were used as an in vitro cell model to characterize replication and pathogenic effects of influenza viruses in PSCs. First, mPSCs and its immortalized cell line mPSCsOct4+ were shown to be susceptible to PR8, seasonal H1N1, 2009 pandemic H1N1, and H7N9 influenza viruses and can generate infectious virus particles, although with a lower virus titer, which could be attributed by the reduced vRNA replication and nucleoprotein (NP) aggregation in the cytoplasm. Nevertheless, a significant increase of interleukin (IL)-6 and interferon (IFN)-γ at 12 h and IFN-β at 24 h post infection in mPSCs implicates that mPSCs might function as a sensor to modulate immune responses to influenza virus infection. In summary, our results demonstrated mPSCs, as one of the target cells for influenza A viruses, could modulate early proinflammatory responses to influenza virus infection.